PEEK Acuity and its Potential to Improve Visual Acuity Screening - Dipayana, Pikasa Retsyah; Firmansjah, Muhammad; Wahyuni, Indri; Nurfahri, Rifat (Universitas Airlangga, 2025)
Introduction: Uncorrected refractive errors contribute to 43% of the leading causes of global visual impairment. Early screening is essential to detect visual impairment and to plan early intervention. Portable eye examination kit (PEEK) Acuity has the potential to help improve early detection; however, its validation needs to be studied. Purpose: To carry out a validation test of PEEK Acuity as a visual acuity examination tool compared to the Snellen Chart. Reviews: PEEK Acuity is a smartphone-based screening modality that can be used offline and has a low false positive rate. Several studies have been conducted to evaluate the accuracy of using the PEEK Acuity application. The duration of examination using PEEK Acuity is also said to be significantly shorter than that of using Snellen Chart in preschool-age children. Conclusions: The PEEK Acuity application can currently be considered a viable alternative for vision screening, especially for widespread screening in both the community and school-aged children who require a high level of specificity to avoid errors in identifying cases.